2011
DOI: 10.3171/2010.12.focus10270
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal versus ventral surgery for cervical ossification of the posterior longitudinal ligament: considerations for approach selection and review of surgical outcomes

Abstract: Ossification of the posterior longitudinal ligament is a common cause of radiculopathy and myelopathy that often requires surgery to achieve decompression of the neural elements. With the evolution of surgical technique and a greater understanding of the biomechanics of cervical deformity, the criteria for selecting one approach over the other has been the subject of increased study and remains controversial. Ventral approaches typically consist of variations of the cervical corpectomy, whereas dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Because cervical spine curvature may be altered by surgery, patients with preoperative instability of the cervical spine and patients presenting with kyphosis are not suitable for posterior surgery. For these patients, posterior fixation is generally necessary to avoid kyphosis progress following posterior surgery [19][20][21], increasing risks to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because cervical spine curvature may be altered by surgery, patients with preoperative instability of the cervical spine and patients presenting with kyphosis are not suitable for posterior surgery. For these patients, posterior fixation is generally necessary to avoid kyphosis progress following posterior surgery [19][20][21], increasing risks to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion or non-fusion spinal cord decompression with anterior or posterior approach can be used as surgical treatment (22,41). Methods of cervical posterior decompression include cervical laminectomy, laminectomy and posterior instrumentation, hemilaminectomy, laminoplasty, and arcocristectomy (2,8,20,42).…”
mentioning
confidence: 99%
“…However, anterior surgery is plagued by a high risk of neurologic decline, CSF leakage, and pseudarthrosis because spinal cord was severely compressed, and the dura was frequently attached to OPLL. 36 Despite this potential risk, the incidence of complications in patients with OPLL has not been fully established because of the relatively small number of patients included in previous studies. 37 A previous report addressed that paraplegia occurred from 0% to 14.3% after ADF.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior approach provides a relatively simple and safe means to decompressing the entire cervical spinal cord. 10,36 However, patients may experience late deterioration because of pro-gressive kyphosis, and expansion of the ossification, especially in patients with preexisting kyphosis. 36 Some studies reported that neurological recovery following ADF was superior to that following posterior decompression.…”
Section: Discussionmentioning
confidence: 99%